2018
DOI: 10.1177/2278533718765533
|View full text |Cite
|
Sign up to set email alerts
|

Celebrity Endorsements and Donations: Empirical Investigation of Impact on Philanthropic Giving

Abstract: This study investigates the effects of celebrity endorsers on donations and views of nonprofits. Celebrity endorsers and their relationships with nonprofits evoke a series of emotions that greatly affect how people perceive and donate to nonprofit organizations. Past research demonstrates the tremendous growth in individual philanthropy and the importance of celebrities as influencers on social media. Data was obtained from a random sample of 277 individuals and subjected to statistical analyses. By studying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 3 publications
1
11
0
1
Order By: Relevance
“…Data for the pre-test were collected via snowball sampling (Biernacki and Waldorf, 1981) in an online questionnaire distributed via email and social network sites. Because age has been shown to influence donations (O’Neil and Schenke, 2007; Peterson et al , 2018; Yen, 2002), a screening question was asked to ensure participants were at least 21 years old. After eliminating respondents ( n = 75) who either failed to complete the survey, did not follow directions or did not meet the age requirement, a final sample size of 235 (75.8%) was evaluated with a mean age of 49.5 ( SD = 16.28) that was 53.6% male.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data for the pre-test were collected via snowball sampling (Biernacki and Waldorf, 1981) in an online questionnaire distributed via email and social network sites. Because age has been shown to influence donations (O’Neil and Schenke, 2007; Peterson et al , 2018; Yen, 2002), a screening question was asked to ensure participants were at least 21 years old. After eliminating respondents ( n = 75) who either failed to complete the survey, did not follow directions or did not meet the age requirement, a final sample size of 235 (75.8%) was evaluated with a mean age of 49.5 ( SD = 16.28) that was 53.6% male.…”
Section: Methodsmentioning
confidence: 99%
“…Research has found demographic variables such as income (Jones and Posnett, 1991), education (Mears, 1992), age (Peterson et al , 2018) and gender (Nichols, 1998) are strong predictors of donation levels. Therefore, it is possible that demographic variables may serve as moderators similar to how involvement is in this study.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Through mass media and social media engagement, marketers use celebrities as “human brands” to create advertising attention, enhance evaluation, and produce favorable donation intentions (Chang & Lee, 2009 ; McCormick, 2016 ) surveyed the donation literature to identify external motivators for donating money and tangible assets and found celebrity endorsements to be among the most important external influences to motivate giving. Peterson et al, ( 2018 ) found that by evoking positive emotions, celebrity endorsements produce stronger donation intentions. To celebrities, the endorsement of donations to the cause is instrumental in improving their popularity, social profile, and income.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…How PCC celebrity endorsement in advertising can influence how prospective contributors perceive and donate to the cause in the traditional sense has been studied by a growing body of empirical research, both in off-line contexts (e.g., Ranganathan & Henley 2008 ; Peterson et al, 2018 ) and online (Panic et al, 2016 ). After ad exposure, potential donors form emotional reactions to the ad that can be either positive, negative, or mixed and that can produce message compliance to regulate emotional outcomes.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%